2002
DOI: 10.1653/0015-4040(2002)085[0552:psarao]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Potency, Spectrum and Residual Activity of Four New Insecticides Under Glasshouse Conditions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
6
18
0
Order By: Relevance
“…These results are in conformity with the previously reported 100% larval mortality in H. armigera caused by Emamectin benzoate by residue contact method resulting in LC 50 of 1.75 µg/mL and LC 90 of 13.08 µg/mL (Parsaeyan et al, 2013 Jansson and Dybas (1996). The LC 50 values in the range of 0.005-0.021 µg/mL were revealed by Argentine et al (2002) 50 -lethal concentration that kills 50% of the exposed larvae, LC 90 -lethal concentration that kills 90 % of the exposed larvae;S.E. = Standard error, χ2 = chisquare, df = degree of freedom;Test samples were transformed into log covariant (log 10 ), p>0.05, level of significance is greater than 0.05, no heterogeneity factor is used in the calculation of confidence limits Table 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in conformity with the previously reported 100% larval mortality in H. armigera caused by Emamectin benzoate by residue contact method resulting in LC 50 of 1.75 µg/mL and LC 90 of 13.08 µg/mL (Parsaeyan et al, 2013 Jansson and Dybas (1996). The LC 50 values in the range of 0.005-0.021 µg/mL were revealed by Argentine et al (2002) 50 -lethal concentration that kills 50% of the exposed larvae, LC 90 -lethal concentration that kills 90 % of the exposed larvae;S.E. = Standard error, χ2 = chisquare, df = degree of freedom;Test samples were transformed into log covariant (log 10 ), p>0.05, level of significance is greater than 0.05, no heterogeneity factor is used in the calculation of confidence limits Table 3.…”
Section: Discussionsupporting
confidence: 92%
“…Present investigations were performed to assess the toxicity of a selective and eco-safe insecticide, Emamectin benzoate against H. armigera. Toxicity of Emamectin benzoate has been studied among different insect species and has been found to possess high toxicity against several lepidopterans, such as H. armigera, H. virescens, Pseudoplusia includens, Plutella xylostella, Spodoptera exigua, Trichoplusia ni, S. frugiperda and S. littoralis (Payne et al, 1999;Argentine et al, 2002;Firake and Pande, 2009). Present study clearly reveals the appreciable larvicidal potential of Emamectin benzoate against H. armigera with respective LC 50 values of 0.269 µg/ mL and 0.043 µg/mL for 24 h and 72 h. Slightly higher LC 90 value of 2.738 µg/mL obtained in the current study can be attributed to the variations and heterogeneity in the population.…”
Section: Discussionmentioning
confidence: 99%
“…S. exigua developed no resistance to moderate resistance to EB, LU, and SP leading to the conclusion that these agents are environmentally safe and could be used in IPM and in pesticide resistance management programmes (Ishtiaq et al, 2012). The toxicity of EB was studied on different insect species and showed high toxic effects in killing a wide variety of lepidopterans (Payne et al, 1999;Argentine et al, 2002;Firake and Pande, 2009). It was shown to be 18-to 80,400-fold more potent against Plutella xylostella (L.), Trichoplusia ni (Hübner), Helicoverpa armigera (Hübner), Heliothis virescens (Fabr.)…”
Section: Insecticidesmentioning
confidence: 99%
“…Lufenuron was approximately 2 times more toxic than flufenoxuron against the 2 nd instar larvae of S.littoralis after 96 hrs of exposure. Argentine et al (2002) reported high toxicity of emamectin benzoate against six species of Lepidoptera (LC 90 ranged from 0.0050 to 0.0218 μg/ml). Previous studies also showed that emamectin benzoate was more toxic than lufenuron and flufenoxuron against the 2 nd , 3 rd and 4 th instar larvae of S. littoralis (Saad et al, 2011).…”
Section: Discussionmentioning
confidence: 99%